IWB-EP: TINJAUAN SISTEMATIS MEKANISME DAN KONDISI BATAS PERILAKU KERJA INOVATIF TERHADAP KINERJA KARYAWAN - Puri Rohmatulloh; Haryadi Utomo; R. Youri Lylie (The Asia Pacific Journal Of Management Studies, 2025)
This study employed a qualitative descriptive approach through a systematic literature review of 29 empirical studies published between 2018 and 2025 across diverse countries and sectors to examine the influence of leadership on innovative work behavior (IWB) and employee performance (EP). The findings indicate that leadership, particularly transformational, ambidextrous, relational, and adaptive styles, consistently enhances IWB, which serves as a key mediator in improving EP. Beyond leadership, individual-level factors, such as creative self-efficacy and work engagement, alongside organizational-level factors, including innovation culture and supportive HR practices, significantly contribute to fostering IWB and enhancing performance outcomes. Digitalization emerges as an additional enabler, facilitating innovation through technology adoption and digital literacy. However, its effectiveness is contingent upon moderating factors, such as leadership support, psychological safety, and employee digital readiness. These results underscore a synergistic interplay among leadership, organizational culture, individual capabilities, and digital transformation in driving innovation and performance. From a managerial perspective, the study highlights the importance of integrated leadership development, innovation-oriented HR policies, and digital capability enhancement programs. Future research should adopt longitudinal and cross-cultural designs, explore emerging work arrangements such as hybrid and remote work, and employ advanced analytics to capture the complex, multilevel interactions that shape IWB and EP. Additionally, attention should be given to sectoral differences, methodological diversity, and measurement consistency to strengthen generalizability and practical applicability.